The Effectiveness of Digital Teaching Materials Based on Google Education to Improve Student's Critical Thinking Ability - Felixtian Teknowijoyo; Putri Wulandari; Gunarhadi Gunarhadi (Teknodika, 2022)
This research aims to develop digital teaching materials based on Google education on physics subjects to improve students' critical thinking skills in Kalam Kudus Christian Junior High School Surakarta. This research method used was research and development to ADDIE development models, including the Analysis, Design, Development, Implementation, and Evaluation stages. The subject of this study was class VIII students of Kalam Kudus Christian Junior High School, with 60 students. Teaching materials and critical thinking skills tests were conducted on class VIII Kalam Kudus Christian Junior High School Surakarta students. The design of this research trial was a one-group pre-test-post-test design. The results showed that the average percentage of material expert validation value was 81%, media expert validation value was 84.5, and critical thinking skills instruments were 80.8%, with very feasible criteria. In limited trials, Google-based digital teaching materials users got an average score from teachers and learners of 80.50% with very practical criteria. Google-based digital teaching materials’ effectiveness in improving critical thinking skills was characterized by differences in learners' critical thinking test results from 65.6 to 80. These results indicate that the digital teaching materials based on Google education developed had valid, practical, and effective criteria to improve learners' critical thinking skills.